PTH-146 Oesophageal Variceal Surveillance - Should Community Hospital Endoscopy Units in Gloucestershire Jump On The 'Band-Wagon'?. (17th August 2016) - Materacki, LB; Hollywood, C; Beech, D
Abstract : Introduction: Patients with liver cirrhosis should engage with a variceal surveillance programme to minimise the risk of variceal bleeding, a major cause of morbidity and mortality. 1 To improve compliance with variceal surveillance it is important to adopt a patient-centred approach and optimise access to endoscopy. Although routine diagnostic upper endoscopy is already established in community hospitals in Gloucestershire safety fears obstruct the provision of variceal surveillance causing potentially unjustified inconvenience to patients. Methods: This double-centre, observational study investigated the safety of endoscopic variceal surveillance in adult cirrhotic patients (age range: 29–90 y) and evaluated the feasibility for service expansion into community hospital endoscopy units. Information was collected retrospectively from an electronic database of patients who underwent elective endoscopic variceal surveillance in Gloucester Royal Hospital or Cheltenham General Hospital from February 2013 to August 2014. The medical notes of patients who underwent variceal banding were evaluated for short-term complications of band ligation and length of hospital stay. Results: 223 patients underwent endoscopy for variceal surveillance during the 18 month study period. Of these patients 12.1% (n = 27) required endoscopic band ligation including 7 patients with history of variceal haemorrhage. All patients underwent endoscopy as a day-case procedure with same-day discharge regardless of the need for band ligation. Variceal band ligation was not associated with any significant complications within 7 days. Conclusion: Endoscopy for variceal surveillance is a safe day-case procedure irrespective of the need for band ligation. The safety concerns obstructing the use of existing endoscopy resources for variceal surveillance in community hospitals in Gloucestershire are unjustified. Broadening access to variceal surveillance represents a cost-effective means to make care more patient-centred. This may improve compliance with variceal surveillance and reduce variceal bleeding in cirrhotics. Reference: 1 Tripathi D, et al . UK guidelines on the management of variceal haemorrhage in cirrhotic patients. Gut 2015;64 (11):1680-1704 doi:10.1136/gutjnl-2015-309262 Disclosure of Interest: None Declared